Hubungan citra tubuh dengan status obesitas, aktivitas fisik dan asupan energi remaja SLTP di Yogyakarta dan Kabupaten Bantul - Noviani Tarigan; Hamam Hadi; Madarina Julia (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2005)
Background: The prevalence of obesity in adolescence, both in industrial and in developing countries, is increasing. This might be due to the fact that globalization has affected the lifestyle and the eating pattern of the adolescents. Apart from related to higher risk of cardiovascular morbidity and mortality, obesity in adolescents might be also related to dissatisfaction of body image.Objective: To asses the association between obesity and body image, and between body image and energy intake and physical activities of junior high school adolescents in the District of Yogyakarta and Bantul.Method: This is a cross-sectional study. Subjects were 96 pairs of 12-15 years old obese and non-obese adolescents, identified in the obesity screening programs in junior high schools in Yogyakarta and Bantul. Subjects were asked to complete 34 questions on body shape image. Energy intake and physical activity data were obtained by food- and physical-activity-frequency questionnaires.Results: Obese adolescents had higher odds to be dissatisfied to their body images compared to their non-obese peers, i.e. Mantel-Haenszel Odds Ratio (95% CI) of 14.6(6.2-34.4). Obese female adolescents had higher odds to be dissatisfied than their male counterparts, OR (95% CI) of 19.5(2.4-15.9) in female and OR (95%CI) of 13.4(5.3 – 33.8) in male adolescents. There were no significant associations between dissatisfaction status with energy intake and time spent on light physical activities. Dissatisfied adolescents tended to spend less time on hard physical activities compared to their satisfied peers.Conclusion: Obese adolescents were more likely to be dissatisfied with their body images compared to their non-obese peers, but the dissatisfaction did not lead to less energy intake and more time spent on harder physical activities.